USAHA GURU MENGURANGI KECEMASAN BELAJAR SISWA DALAM PEMBELAJARAN PAI - Idi Warsah; Eko Carles; Ruly Morganna; Sela Anggraini; Shella Silvana; Siti Maisaroh (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
This study aims to explore the forms of anxiety frequently experienced by students in facing religious learning at MAN Rejang Lebong, as well as the efforts made by teachers to overcome student anxiety. The study sample consisted of one Islamic Education teacher and one student from grade X at MAN Rejang Lebong. Data was collected through interviews with teachers and students and analyzed using descriptive qualitative analysis techniques. The results showed that the forms of student anxiety in facing religious learning included a lack of interest in learning about religion, lack of mastery of the material, nervousness and trembling, fear that distracts students during learning, lack of confidence in learning religion, as well as anxiety and worry. The teacher's efforts to overcome student anxiety were by instilling more efficient learning concepts, providing regular exercises, and using varied learning models. As a recommendation, it is suggested for teachers and parents to motivate and pay more attention to students so that they can study diligently even outside of school. This is expected to improve the readiness of students to face religious learning at school. In conclusion, this study provides helpful information for teachers and parents in helping students overcome anxiety in learning religion